Kajian hidrologi dan hidrogeologi daerah penambangan, studi kasus lipatan sinklin di Sungai Mahakam, Kutai Kartanegara , Provinsi Kalimantan Timur - Shalaho Dina Devy; Ibnu Hasyim (SPECTA Journal of Technology, 2022)
Changes in land use due to open pit mining operations, indirectly affect the hydrological cycle. Open pit mining operations, especially the open pit method, greatly affect subsurface conditions, such as lithology and hydrogeology. The purpose of this study was to analyze the hydrological and hydrogeological conditions before mining on syncline folds in the Mahakam river. This research is an inductive research with an analytical approach which includes the study of land use, hydrological conditions, geology, and hydrogeology. The land use of the research area is dominated by plantations (84%) with a rain catchment area of ​​995.9 hectares. The results of the hydrological analysis yielded daily rainfall values ​​with a 5-year recurrence of 208.4 mm, annual rainfall of 2.177.32 mm, runoff 238.63 mm/yr, evapotranspiration 1,031.16 mm/yr and groundwater recharge 907.53 mm/th. The lithology of the study area is dominated by sandstone and clayey siltstone. The results of the aquifer test (pumping test) showed that the average K value (hydraulic conductivity) of sandstone was 1.33 × 10-2 m/s and claystone was 6.77 × 10-10 m/s. The results of the hydrogeological analysis show that the top layer is an aquitard, below it is an aquifer, then an aquitard, and the bottom is an aquiclude. The type of aquifer in the study area is classified as semi confined aquifer